Revitalisasi Kajian Botani dalam Pendidikan untuk Mendukung Sustainable Development Goals - Anisa; Thahir, Rahmatia; Hambali, Hilmi; Magfirah, Nurul; Fadhilah, Nurul; Mahmudah, Rafiah; Irmawanty; Sativani Hayati, Riza; Nurdiyanti; Safitri, Dian; Wajdi, Muhammad (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This community service activity was motivated by the need to strengthen botanical studies in biology education so that it is not only understood as conceptual material, but also as a means to build environmental literacy and sustainability awareness. This activity aims to improve the understanding and skills of Biology Education students as prospective teachers in integrating botanical studies with the issue of Sustainable Development Goals or SDGs. The activity was held on May 7, 2026, at the Minihall FKIP Universitas Muhammadiyah Makassar, involving 50 Biology Education students. The implementation method used a participatory-educational approach through the stages of preparation, material delivery, interactive discussions, mentoring in developing sustainability-based botanical learning ideas, and activity evaluation. The results of the activity showed that participants gained a better understanding of the relationship between botany and SDGs, the potential of local plants as learning resources, and the importance of contextual, applicable, and sustainability-oriented botanical learning. Participants were also able to develop initial ideas for learning or educational media for botany based on local potential and environmental issues. This activity provides benefits in strengthening plant literacy, environmental literacy, and pedagogical readiness of prospective biology teachers. Thus, revitalizing botanical studies in education can be a strategy to strengthen sustainable education that supports the achievement of the SDGs.